6-methoxy-8-[[6-methoxy-8-[[6-methoxy-2-methyl-1-(2methylpropyl)-3, 4-dihydro-1h-isoquinolin-7-yl]oxy]-2-methyl-1(2-methylpropyl)-3, 4-dihydro-1h-isoquinolin-7-yl]oxy]-2-methyl1-(2-methylpropyl)-3, 4-dihydro-1h-isoquinolin-7-ol time-resolved absorption and resonance ft-ir and raman biospectroscopy and density functional theory (dft) investigation of vibronic-mode coupling structure in vibrational spectra analysis. Issue 3 (2019) - Heidari, Alireza; Esposito, Jennifer; Caissutti, Angela
No abstract available